PERAN KEPALA SEKOLAH DAN GURU DALAM PENGEMBANGAN DAN PENERAPAN KURIKULUM 2013 PAUD - Vera Novita Sari; Ocih Setiasih; Rudyanto Rudyanto (Sekolah Tinggi Agama Islam (STAI) Al Hidayah Tasikmalaya, 2020)
The curriculum is a component in education that is used as a guideline for implementing a learning in any educational institution. Currently the early childhood curriculum that applies in TK Negeri Pembina Sukamara is the curriculum 2013, where the development of this curriculum is to improve the mindset, strengthening governance, deepening material, strengthening learning processes and adjusting learning load. The key to the success of a curriculum is inseparable from the role of the Principal and Teacher. The Principal acts as the leader who is responsible for all matters relating to the smooth running of the school, as well as the teacher's role to be able to convey learning that has been applied in the curriculum. This research uses qualitative case study research, which is the researcher conducts in-depth interviews with the principal, two teachers and one representative from the school committee. Based on the data found, TK Negeri Pembina Sukamara has developed and implemented the 2013 curriculum, from begining to do the analysis, document preparation, ratification and implementation of the curriculum 2013 Early childhood education in accordance with applicable references. As for the implementation there are several supporting factors such as the cooperation of all the teams in the school and adequate infrastructure, in addition to supporting factors there are also inhibiting factors, namely uneven and sustainable curriculum socialization resulting in a lack of teacher creativity.